Para além de pioneiros e forasteiros : outras histórias do oeste do Paraná - Langaro, Jiani Fernando (2006)
The present essay has the purpose of discussing the many memories in dispute in the West of Paraná, having as base the Municipal District of Santa Helena and other stories that emerge from this tension. Produced in different moments, those versions refer to social processes developed between 1950 and 2005 and relate the place to the regional. I approach, at first, the constitution process of a memory in the public sphere of Santa Helena, working with sources as History books, monuments, press material and also material for divulgation of the local public power. Usually constituted by the "elites" of the place, that version expresses projects elaborated for the municipal district. I accomplish a relational study, starting from the look given by workers that live in the municipal district, about their life trajectories. I take their narratives as live testimonies of the memory and place privileged to capture, in the place, the many versions in dispute. These subjects, then, carry out a transit, among the different ways of perceiving the past and establish themselves in the place, starting from their memories. By crossing oral sources, journalistic materials and some photographs, I seek to observe the other stories that are constituted in this dispute. I approach the ways of living and working, locally constituted, in which many workers associate rural and urban elements, at the same time that they constitute, in a diverse and even contradictory way, a border between the countryside and the city. I talk about the ways by which they use their remembrances, intending to reference projects and demands, which are particular to them. Their reminiscences are constituted, thus, in instrument of social struggle, having as main focus the demanding for the local richness, represented by the land in the seventies and, from the nineties on, by the royalties paid by Itaipu power plant to Santa Helena City Hall. I observe, moreover, starting in the nineties, a change occurred in relation to the work in those memories. In the versions produced in the public sphere, it is no longer a convergent center, but the notion of "development" occupies this spot. In the workers narratives the labor is presented, but the main focus of the narratives reverts to the access to the local richness, mediated by the public power. Such factor points to the historicity of these memories and to its constitution among the social relations.